2019
DOI: 10.3389/fmed.2019.00064
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Sputum Specimens as a Predictor of Isolated Bacteria From Patients With Lower Respiratory Tract Infections at a Tertiary Referral Hospital, Denpasar, Bali-Indonesia

Abstract: Sputum quality is crucial in finding infectious bacteria that will be used to guide definitive antibiotic therapy. Errors in reporting isolated bacteria will affect the rate of patients' morbidity, mortality, and increase patient care costs. This study aims to find out the relationship between sputum quality and isolated bacteria at a Tertiary Referral Hospital, Denpasar, Bali-Indonesia. The study was conducted for 6 months in the Sanglah Hospital Clinical Microbiology laboratory. There were 726 sputum specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
(22 reference statements)
5
9
0
Order By: Relevance
“…Our data also showed that more than 73% of sputum and about 70% of bronchial wash specimens generated non-pathogenic bacterial growth, and this may indicate the presence of normal flora in the collected specimens (Budayanti, et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…Our data also showed that more than 73% of sputum and about 70% of bronchial wash specimens generated non-pathogenic bacterial growth, and this may indicate the presence of normal flora in the collected specimens (Budayanti, et al, 2019).…”
Section: Discussionsupporting
confidence: 63%
“…33 In this study, the most common bacteria found was Klebsiella pneumoniae. This is consistent with research in various regions in Indonesia, including Padang, 34 Bali, 35 and Lampung. 36 The difference in the characteristics of the main causative bacteria is answered by a report from a systematic review where although Streptococcus pneumonia is the most common cause, its prevalence varies from 4 to 24%.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the large increase of calcitonin will reflect the overlapping infection of bacteria in patients who have developed serious diseases, leading to the complication of clinical conditions (Martins-Filho et al 2020 ). In addition, the microbiological examination is a practical way for diagnosis, especially sputum culture (Budayanti et al 2019 ). However, taking sputum or blood samples from SARS-CoV-2–infected patients may pose a significant risk to biological sample collectors and laboratory technicians as the SARS-CoV-2 does not only spread through respiratory droplets and direct contact but also through virus-laden aerosols (Peng et al 2020 ; Xu et al 2020 ).…”
Section: Bacterial and Fungal Coinfection With Sars-cov-2mentioning
confidence: 99%